If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4 + 3x = 2x + 3 Reorder the terms: 4 + 2x + 3x = 2x + 3 Combine like terms: 2x + 3x = 5x 4 + 5x = 2x + 3 Reorder the terms: 4 + 5x = 3 + 2x Solving 4 + 5x = 3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 4 + 5x + -2x = 3 + 2x + -2x Combine like terms: 5x + -2x = 3x 4 + 3x = 3 + 2x + -2x Combine like terms: 2x + -2x = 0 4 + 3x = 3 + 0 4 + 3x = 3 Add '-4' to each side of the equation. 4 + -4 + 3x = 3 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 3 + -4 3x = 3 + -4 Combine like terms: 3 + -4 = -1 3x = -1 Divide each side by '3'. x = -0.3333333333 Simplifying x = -0.3333333333
| 40+40y-16=13y-12-3y | | 36=3.14(4)h | | 7x-2y=-26 | | 5g+4(-5+3g)=11g | | y-1+4(3y+1)=-3(y+5) | | .4(x+2.4)=2.95 | | x=2(x-1)-6 | | -36-9=x | | 6x-2=8+5x | | 2x^2-26x+7=0 | | -5x=-33 | | 2X+3-(x-1)=2x-(-2)-(-x) | | 3/10-2x=8/2x | | 8.3=(b/14) | | 1/2(20x)-18=200 | | 4(x+5)+84=8x-4(x-6) | | [(-24)+(-8)]+13= | | -2(11)-15y=-29 | | (27b^4)^(7/3)/(9b^5)^(3/2) | | 4x-1+6=180 | | 1/5n-8=95 | | 40l-2=7 | | (-2/3)/[1/2-(1/9)] | | -2x-6+-.25x-3+90=180 | | 44=t/12 | | 1x=2x+6 | | 6x^2-7x-54= | | 2(3b+4)=68 | | -2(-41)-6+-.25(-41)-3+90=180 | | 6a+110b-20= | | (5x-16)= | | 8x*-4=5 |